Multiple sclerosis in children and adolescents: incidence and clinical picture – new insights from the nationwide German surveillance (2009–2011). (28th January 2014) - Reinhardt, K.; Weiss, S.; Rosenbauer, J.; Gärtner, J.; von, R.
<x xml:space="preserve">Abstract</x> Background and purpose Pediatric multiple sclerosis (MS) clinical and incidence data have been reported for several countries but valid age dependent incidence data are not yet available. The true incidence of pediatric MS in Germany was estimated and the clinical characteristics at diagnosis according to the 2005 McDonald criteria are described. Methods Between 2009 and 2011 active prospective nationwide surveillance for MS in children and adolescents ≤15 years included all pediatric hospitals, MS centers and private practices specialized in MS. Data were adjusted for under‐reporting by capture−recapture from an independent second source. Results The estimated incidence of pediatric MS was 0.64 per 100 000 person‐years with clear increase from age group ≤10 (0.09/100 000) to 2.64 per 100 000 in age group 14−15 years. All had relapsing−remitting disease with polysymptomatic onset in half of the cases. Spinal MRI with positive findings in two‐thirds of patients contributed to diagnosis. Conclusion Using an active prospective surveillance system and the McDonald criteria for first MS diagnosis the age‐related incidence of pediatric MS in Germany was uncovered and is more common than in previous estimates. Thorough application of McDonald criteria and inclusion of spinal MRI data allowed for early diagnosis in almost 90% of cases.